Pétro-puissance et système mondial : le cas de l’Arabie saoudite - Korany, Baghat (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1979)
Despite Us increasing weight in the global System, the international repercussions of Saudi petro-power are very under-researched. This study starts with a critical evaluation of the literature on the underdeveloped study of underdeveloped countries. The author then elaborates his research framework, defines and operationalizes his main concepts, and explicits two main hypotheses concerning the international status and the political role of Saudi Arabia. The study proceeds then to empirical verification. Eight tables, data analysis of recent Saudi international initiatives, and some interviews with Saudi and U.S. policy makers support the author's thesis : Saudi political elite works actively to maintain the basic structures of the contemporary global System.